PENENTUAN PENERIMA BEASISWA DENGAN ALGORITMA FUZZY C-MEANS DI UNIVERSITAS MEGOW PAK TULANG BAWANG - -, Muhardi; -, Nisar (244-5567)
The scholarship is the grant in the form of financial assistance given to an individual who intends to use for the sake of the continuity of education traveled. Determination of the scholarship can be grouped based on the criteria of the cumulative Achievement Index (IPK), the level of poverty,dependent parent and student achievement in the process of recruitment of scholarship. Fuzzy CMeans algorithm is an algorithm that is easily and often used in grouping data because making an estimate of efficient and doesnt require a lot of parameters. Some research has resulted in the conclusion that the Fuzzy C-Means method can be used to classify data based on certain attributes.Application of Fuzzy C-Means algorithm in determination of scholarship in kelompokan into three clusters, namely receiving, considering and not eligible to receive the scholarship, sempel 75 student data sebenyak data retrieved three clusters based on the average value of the determination of a scholarship then each cluster are classified according to criteria which is more prioritized with the greatest value at the end of the cluster is receiving a scholarship, whereas the smallest value cluster is a cluster that is not eligible to receive the scholarship.Keywords: scholarship, clustering, Fuzzy C- Means